(untitled) (Journal of the College of Basic Education, 2022)
The British position on the conflict between the Emir of Najd and Al-Ahsa and the Emirs of Hail (), the allies of the Ottoman Empire, and the role of Percy Cox () in its course (1915-1918):Hail continued to pose a threat to the Emirate of Najd after Abdulaziz bin Saud entered Riyadh in 1902, and the subsequent imposition of his control over Najd and its neighboring regions (Al-Kharj, Al-Aflaj, and Wadi Al-Dawasir), and Ibn Saud () became so strong that Ibn Rashid asked for aid. In 1904 from the Ottomans to confront the Najdi threat (), and to confront that, Ibn Saud established Al-Artawiyah () in 1912 - within an area that controls the trade route, which represents the most important source of funding for Najd, especially in Kuwait, and also ensures that the Al-Rasheed family in Hail is not connected to the Ottomans in Al-Ahsa - In order to prevent any attack from Shammar district, or from Iraq